2018
DOI: 10.1093/mnras/sty3029
|View full text |Cite
|
Sign up to set email alerts
|

SPLOT: a snapshot survey for polarized light in optical transients

Abstract: We present SPLOT, a small scale pilot survey to test the potential of snapshot (single epoch) linear imaging polarimetry as a supplementary tool to traditional transient follow-up. Transients exist in a vast volume of observational parameter space and polarimetry has the potential to highlight sources of scientific interest and add value to near real-time transient survey streams. We observed a sample of ∼ 50 randomly selected optical transients with the EFOSC2 and SofI instruments, on the 3.6m New Technology … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 89 publications
2
6
0
Order By: Relevance
“…This high level of polarization was interpreted as arising in a relativistic jet-like outflow. Higgins et al (2019) reported a single epoch of V-band polarimetry of OGLE16aaa, measuring 1.81 ± 0.42 per cent, which is of similar magnitude to the polarization measured for ASASSN-15lh by us. Lee et al (2020) observed an evolution in the polarization of AT 2019dsg, with the degree of polarization decreasing from 9.6 ± 2.6percent (at 4 d after light-curve maximum) to 2.0 ± 1.0 per cent (34 d later).…”
Section: Discussionsupporting
confidence: 79%
“…This high level of polarization was interpreted as arising in a relativistic jet-like outflow. Higgins et al (2019) reported a single epoch of V-band polarimetry of OGLE16aaa, measuring 1.81 ± 0.42 per cent, which is of similar magnitude to the polarization measured for ASASSN-15lh by us. Lee et al (2020) observed an evolution in the polarization of AT 2019dsg, with the degree of polarization decreasing from 9.6 ± 2.6percent (at 4 d after light-curve maximum) to 2.0 ± 1.0 per cent (34 d later).…”
Section: Discussionsupporting
confidence: 79%
“…The degree of polarization was further corrected for bias using the Modified ASymptotic (MAS) estimator of true polarization p MAS (Plaszczynski et al 2014). We follow Higgins et al (2019) by characterizing polarization measurements with p MAS /σ p < 3 as nondetections, and quote the 95 per cent upper limit.…”
Section: Data Analysis Workflowmentioning
confidence: 99%
“…Polarimetric observations of "ordinary" optical TDEs (van Velzen et al 2020) were scarce until recently, including few measurements of individual events (Higgins et al 2019;Lee et al 2020;Holoien et al 2020). Leloudas et al (2022) gathered spectral polarimetry for a sample of three optical TDEs and demonstrated that the continuum polarization is wavelength independent, while emission lines depolarize the spectrum.…”
Section: Discussionmentioning
confidence: 99%